A Labeling Strategy for Living Specimens in Long-Term/Super-Resolution Fluorescence Imaging - Han, Yubing; Zhang, Zhimin; Liu, Wenjie; Yao, Yuanfa; Xu, Yingke; Liu, Xu; Kuang, Cuifang; Hao, Xiang (Frontiers in Chemistry, 2021)
Despite the urgent needs of imaging living specimens for cutting-edge biological research, most of the existing fluorescent labeling methods suffer from either poor optical properties or complicated operations to realize cell-permeability and specificity. Here, we introduce a method to overcome this tradeoff by incubating living cells and tissues with bright and photostable fluorescent dyes, no matter if they are cell-permeable or not, at particular conditions (concentration and temperature) without physical cell-penetration or chemical modifications. Particularly, using Atto 647N to replace the most-commonly-used red-absorbing SiR dye in live-cell long-term imaging, we obtain 2.5-time enhancement on fluorescence brightness and photostability. These improvements give access to the discovery of a new interaction model between endoplasmic reticulum and mitochondria. These results indicate the great potential of using dyes, which are normally considered “live-cell incompatible”, to capture the morphology and dynamics of subcellular structures in living specimens. Our strategy has expanded the scientist’s toolbox for understanding the dynamics and interactions of subcellular structures in living specimens.